Pengaruh Laporan Arus Kas Terhadap Tingkat Likuiditas (Studi Kasus Pada Lembaga Pembiayaan Di Bursa Efek Indonesia 2013-2017) - Yogi Atmadijaya; Hilda Purnamawati; Iyan Sukiman (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2020)
The research method used is a quantitative method with cuantitavie descriptive. The population in this study were all publicly listed companies listed on the Indonesia Stock Exchange in 2013-2017, the sampling technique used was purposive sampling and the samples taken were 12 financial institutions. The data analysis technique in this study is panel data regression analysis usingEviews. The test results show that in 2013-2017 the development of cash flows in 12 financial institutions fluctuated, with the highest average occurring in 2015. The development of the level of liquidity in 12 financial institutions tended to fluctuate with the highest liquidity level was 2014 Danasupra Erapacific Tbk. Partially cash flows from operating activities have a significant effect on the level of liquidity of financial institutions in 2013-2017. Partially the cash flows from investment activities have no significant effect on the level of liquidity of financial institutions in 2013-2017. Partially cash flows from funding activities have a significant effect on the level of liquidity of financial institutions in 2013-2017. Simultaneously, cash flows that feel from operating, investing and funding activities have a significant effect on the level of liquidity of financial institutions in 2013-2017 with a magnitude of influence of72.7%